Crosstalk between neutrophil extracellular traps and immune regulation: insights into pathobiology and therapeutic implications of transfusion-related acute lung injury - Liu, Yi; Wang, Rong; Song, Congkuan; Ding, Song; Zuo, Yifan; Yi, Ke; Li, Ning; Wang, Bo; Geng, Qing (Frontiers in Immunology, 2023)
Transfusion-related acute lung injury (TRALI) is the leading cause of transfusion-associated death, occurring during or within 6 hours after transfusion. Reports indicate that TRALI can be categorized as having or lacking acute respiratory distress syndrome (ARDS) risk factors. There are two types of TRALI in terms of its pathogenesis: antibody-mediated and non-antibody-mediated. The key initiation steps involve the priming and activation of neutrophils, with neutrophil extracellular traps (NETs) being established as effector molecules formed by activated neutrophils in response to various stimuli. These NETs contribute to the production and release of reactive oxygen species (ROS) and participate in the destruction of pulmonary vascular endothelial cells. The significant role of NETs in TRALI is well recognized, offering a potential pathway for TRALI treatment. Moreover, platelets, macrophages, endothelial cells, and complements have been identified as promoters of NETs formation. Concurrently, studies have demonstrated that the storage of platelets and concentrated red blood cells (RBC) can induce TRALI through bioactive lipids. In this paper, recent clinical and pre-clinical studies on the pathophysiology and pathogenesis of TRALI are reviewed to further illuminate the mechanism through which NETs induce TRALI. This review aims to propose new therapeutic strategies for TRALI, with the hope of effectively improving its poor prognosis.